(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
This paper presents optimal power flow and short circuit analysis of an IEEE-14 bus system using the Electrical Transient Analyzer Program (ETAP) software. The load flow and short circuit studies in power systems are very important for both design and operating stage performance evaluation, as well as ensuring dependable grid operations through appropriate protection scheme settings. In addition, a comparison between load flow analysis and its optimal load flow analysis, then the short circuit evaluations are carried out It is employed to determine the greatest and lowest fault currents for 3-phase and single-line to ground faults on different buses. Inductive loads that connect to the electrical system generally consume reactive power. Load flow analysis is used to calculate the voltage, the real power, and also the reactive power flow over each bus. Optimal power flow analysis is frequently used to reduce a system’s fuel expenditures by minimizing actual and reactive power losses. In order to calculate protective device ratings, the IEEE-14 bus system uses maximum and minimum short circuit currents, also known as sub-transient and steady-state fault currents